Exploring the characters and values developed from psychology students’ experiential learning during internship at psychiatry clinic - Mansor, Afiqah Syahirah; Mohamad Nawi, Nurul Ain Nabilah; Ahmad Basri, Nadzirah; Abdul 'Azzam, Ummu Zakirah (Faculty of Medicine, UiTM, 2024)
Background: This qualitative study explores the character and values developed from exposure towards experiential learning psychology students gained through their internships at psychiatry clinic in a Malaysian university hospital. The research aims to identify how students view the relationship between their experiential learning experiences and their psychological well-being and identify activities that most effectively instil positive character strengths in these students. Method: Using a grounded theory approach, data was collected through the document analysis of written reflections submitted by final-year psychology degree students and second-year clinical psychology master students from various Malaysian universities at the end of their internship. The sample size was 9 students. It was determined through theoretical sampling, with data collection continuing until theoretical saturation was achieved. Results: Three themes emerged from the analysis: (1) the nurturing workplace environment, (2) the empowerment gained from experiential learning, and (3) personal growth through direct engagement with clients. Conclusion: The findings of this study are expected to enhance the understanding of how experiential learning in psychiatry settings affects the mental well-being of psychology students and the development of character strengths. These insights would be valuable for supervisors that oversee psychology interns; contributing to the design of more effective supervision practices that nurture students’ well-being and professional growth.